PEMANFAATAN ECENG GONDOK SEBAGAI BAHAN KERAJINAN TANGAN DI DESA KASERANGAN KECAMATAN PONTANG KABUPATEN SERANG - Suryapermana, Nana; Fauzi, Anis; Subekhan, Mochammad (Yayasan Education and Social Center, 2024)
In daily life, the people of Kaserangan Village still actively use the river flow for their daily needs, such as washing clothes, washing dishes, bathing and even washing food. Meanwhile, the water used has been polluted by rubbish that people throw into the river, so it is no longer suitable for use for all daily needs. This research uses a survey method with descriptive analysis techniques. The objectives of this service to the community of Kaserangan Village, Serang Regency, Banten Province are as follows: First, increase creativity, thinking and acting in the development of knowledge for both lecturers and students; Second, understand village management in the working mechanisms in the community; and Third, knowing the condition of rural communities spread across Serang Regency. The results show that the people of Kaserangan Village are actually people who are very active in village development activities. They have high motivation for something new, are actively present and accept it with open arms. They are able to produce woven souvenirs from Water Hyacinth, in the form of pins, key chains and brooches